2008
DOI: 10.1007/s00421-008-0924-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of protective clothing on energy consumption during different activities

Abstract: Protective clothing (PPC) can have negative effects on worker performance. Currently little is known about the metabolic effects of PPC and previous work has been limited to a few garments and simple walking or stepping. This study investigated the effects of a wide range of PPC on energy consumption during different activities. It is hypothesized that wearing PPC would significantly increase metabolic rate, disproportionally to its weight, during walking, stepping and an obstacle course. Measuring a person's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(147 citation statements)
references
References 11 publications
6
134
2
5
Order By: Relevance
“…The higher weight of the Scott clothing thus is an issue, but would not be enough to explain the observations. Recent work by Dorman and Havenith [1] has demonstrated that weight is only one part of the effect of clothing on metabolic energy consumption. They observed how clothing stiffness, layering and bulkiness can add dramatically to the load.…”
Section: Special Issues: Scott and Amundsenenergy Consumption Issuesmentioning
confidence: 99%
“…The higher weight of the Scott clothing thus is an issue, but would not be enough to explain the observations. Recent work by Dorman and Havenith [1] has demonstrated that weight is only one part of the effect of clothing on metabolic energy consumption. They observed how clothing stiffness, layering and bulkiness can add dramatically to the load.…”
Section: Special Issues: Scott and Amundsenenergy Consumption Issuesmentioning
confidence: 99%
“…During this investigation an average increase of 19 8 and 16 1 in prod was exhibited when wearing BOILER compared to SHORTS and WBL, respectively, however prod was subject to large individual variation. This is a greater rise than that noted by Dorman & Havenith (2009), however other factors are likely to have influenced this increase in addition to the weight of the garments, for instance the material type, the air layers created, and the material thickness. The greater the garment thickness the slower the rate of perspiration and moisture vapour transfer to the garment surface (Roberts et al 2007).…”
Section: Perceptual Strainmentioning
confidence: 69%
“…Heavier garments result in increased metabolic rate, with a 2.7% increase per kg of clothing weight having previously been suggested (Dorman & Havenith 2009), consequently increasing the physiological strain an individual experiences. During this investigation an average increase of 19 8 and 16 1 in prod was exhibited when wearing BOILER compared to SHORTS and WBL, respectively, however prod was subject to large individual variation.…”
Section: Perceptual Strainmentioning
confidence: 93%
“…However, it may be difficult to estimate the need for the required number of garments for various environmental conditions. Another problem is related to increased bulk of a clothing ensemble with a greater number of garments, which will limit body movement, manual dexterity and reduce human performance [11]. This review describes five types of PHGs; it analyses and discusses their advantages and disadvantages.…”
Section: Methods For Keeping Thermal Comfortmentioning
confidence: 99%